Causes of Menorrhagia in Females Between 21-50 Years of Age Attending the Out Patient Department of Naseer Teaching Hospital - Ara, Anjum; Rahim, Naheed (Journal of Gandhara Medical and Dental Science, 2015)
OBJECTIVES: To determine the causes of menorrhagia MATERIAL AND METHODS: This case series study was conducted in the department of obstetrics and Gyneacology Naseer Teaching Hospital Peshawar over a period of one year from June 2006 to May 2007. Eighty patients with menorrhagia were studied between ages of 21-50 years. All patients were thoroughly investigated for the causes of menorrhagia. All the patients having menstrual blood loss of more than eight days or history of passage of clots or having hemoglobin less than l0g/ dl were included in the study and patients having pubertal menorrhagia, less than 20 years of age or postmenopausal patients, on hormonal replacement therapy were excluded from the study. RESULTS: Out of total eighty patients, the commonest age group was above 40 years i.e.63.75% (n=51). The most common cause of menorrhagia was fibroid uterus in 47.5% (n=38) cases followed by adenomyosis in 25% (n=20) cases, endometrial polyp in 7.5% (n=6) cases, endometrial hyperplasia in 6.25% (n=5) cases, injectable progestogens in 6.25% (n=5) cases, intrauterine contraceptive device in 5% (n=4) cases. 30 patients (37.5%) were multipara, 25 (31.25%) were grand multipara and 25 (31.25%) were great grand multipara.All of them were anemic. Severe anemia (hemoglobin < 6 gm%) was found in one case (1.25%), moderate anemia (hemoglobin 6-8 gm%) in 45 cases (56.25%) and mild anemia (hemoglobin 8-10 gm%) in 34 cases (42.75%). Abdominal ultrasound alone was done in 63 cases (70.75%), and transvaginal ultrasound in 17 patients (21.25%). The diagnosis of fibroid uterus, endometrial polyp and endometrial hyperplasia was confirmed on ultrasound. CONCLUSION: In my study fibroid uterus (47.5%), adenomyosis (25%), endometrial polyp (7.5%) and endometrial hyperplasia (6.25%) were the common causes in patients presenting with menorrhagia to Naseer Teaching Hospital causing disruption and psychological problem for females.